Forensic Pathology and Unnatural Death Investigations: A Systematic Review of Case Studies and Procedures - Almakrami, Hussain Abdullah Hassan; alsogoor, Hamad mahdi Saleh; Alsulayyim, Teflah Saeed Ali; Alhokash, Hadi Abdullah Hadi; jali, Abdullah saleh ali; lasloum, saleh obeid hadi; Al Sallum, Dhafer Obaid Hadi; AlHarmes, Hadi Salem Nasser; HUMAYYIM, SAEED AWADH ALI BANI; ALTALAILI, TALAL ALLAS MAHDI (Journal of Ecohumanism, 2024)
Forensic pathology plays a crucial role in investigating unnatural deaths, providing insights that influence legal and judicial outcomes. This systematic review examines case studies and procedures in forensic pathology to identify common methodologies, challenges, and trends in unnatural death investigations. By analyzing a selection of case studies across various regions and types of deaths, including homicide, suicide, and accidental deaths, this review highlights the standard forensic techniques employed—such as autopsy, toxicology, DNA analysis, and imaging technologies—and discusses their impact on case resolution. Findings indicate significant advancements in technology and methodology, yet also reveal challenges such as jurisdictional variations, resource limitations, and inconsistencies in procedure standardization. This review underscores the need for uniform forensic protocols to improve investigative outcomes and legal accuracy. Recommendations include adopting standardized practices, improving resource allocation, and encouraging further research into underexplored areas of forensic pathology. This work aims to provide forensic professionals, policymakers, and researchers with insights that contribute to the refinement of death investigation procedures and support the justice system.